Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1515/hsz-2015-0244
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical and biochemical regulation of cathepsin K expression in endothelial cells converge at AP-1 and NF-κB

Abstract: Cathepsins K and V are powerful elastases elevated in endothelial cells by tumor necrosis factor-α (TNFα) stimulation and disturbed blood flow both of which contribute to inflammation-mediated arterial remodeling. However, mechanisms behind endothelial cell integration of biochemical and biomechanical cues to regulate cathepsin production are not known. To distinguish these mechanisms, human aortic endothelial cells (HAECs) were stimulated with TNFα and exposed to pro-remodeling or vasoprotective shear stress … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 41 publications
1
5
0
Order By: Relevance
“…The induction of GM‐CSF production in T cells involves the activation of both NF‐κB and NFAT2 . The activation of NF‐κB pathway was also reported in TNF‐α‐ and IL‐17A‐induced activation of synovial fibroblasts and endothelial cells . In our study, we revealed that the same synergistic activation of NF‐κB and NFAT2 promoted IL‐17A‐induced GM‐CSF production in Sca‐1 + cardiac fibroblasts.…”
Section: Discussionsupporting
confidence: 82%
“…The induction of GM‐CSF production in T cells involves the activation of both NF‐κB and NFAT2 . The activation of NF‐κB pathway was also reported in TNF‐α‐ and IL‐17A‐induced activation of synovial fibroblasts and endothelial cells . In our study, we revealed that the same synergistic activation of NF‐κB and NFAT2 promoted IL‐17A‐induced GM‐CSF production in Sca‐1 + cardiac fibroblasts.…”
Section: Discussionsupporting
confidence: 82%
“…This is different from literature that shear stress can cause marked changes in NF-jB activation. 28,38,57 This could be due to the relatively short duration of mechanical stimulation in the present study (1 h vs. 8, 12 or 24 h in other studies). In our future studies, we will need to increase the duration of mechanical stimulation to address this limitation.…”
Section: Discussionmentioning
confidence: 66%
“…Shear stress constitutes a tangential mechanical force that fluctuates at regular intervals in response to the heart's pumping action. Variations in the amplitude and frequency of shear stress within arteries are linked to a wide variety of processes in cardiovascular wellness and disease [ 28 , 29 ]. The expression of Cats is inhibited and the vascular morphology is preserved when the shear force is stable [ 30 ].…”
Section: Cats Are Involved In All Phases Of Stent-related Restenosismentioning
confidence: 99%
“…Philip and colleagues observed that the disturbance of blood flow and the presence of tumor necrosis factor alpha (TNFα) led to an increase in the expression of CaK and V in endothelial cells after stent implantation. Conversely, the application of vascular protective shear stress appeared to mitigate the activation of the JNK/c-jun signaling pathway, which in turn limited the activation of CatK by inhibiting the NF-κb pathway [ 28 ]. In an experiment with diabetic rats, it was discovered that laminar flow decreased the activity of CatL produced by endothelial cells, decreased the conversion of latent heparinase into active heparinase, and affected lipoprotein lipase (LPL), thereby influencing myocardial cell metabolism [ 29 ].…”
Section: Cats Are Involved In All Phases Of Stent-related Restenosismentioning
confidence: 99%
See 1 more Smart Citation